Dental crowding as a possible indicator of inadequate oral hygiene - Sernaque Roca, Katharine Maribel (2021)
In the study the authors concluded that there was no correlation between dental crowding and oral hygiene. However, the results of the study could vary, if selection biases are avoided, which occurred when including within the sample, people who did not have the main characteristic of crowding